Parental Assistance with Assignments - Types of Parental Involvement in Homework - Mária-Magdolna Szász (Debrecen University Press, 2023)
The present study analyses - using qualitative methods - parental involvement in children's homework, the forms of parental involvement and the types of parents in the studied area, emphasizing the decisive role of parents in the educational life of their children, using the sample of several rural settlements in Szeklerland. By focusing on the rural context, this research contributes to the existing literature by offering a more nuanced understanding of parental involvement, potentially uncovering challenges and strategies that are unique to rural communities. The literature lacks a parent typology based on qualitative research. The most common types of parents are: "aversive", " ambitious ", "partner", "accountable", "networking". The benefits of parental support for children's learning at home have been widely emphasized by experts in recent research. Active parental involvement has a positive impact on student achievement and learning. It also gives parents a better insight into school life and enables them to develop a partnership with the teachers.